Enhancing students’ well-being and studying in higher education: a comparison of two different study skill courses - Katajavuori, Nina; Hailikari, Telle; Asikainen, Henna (Frontiers in Education, 2025)
IntroductionUniversity students face many challenges during their studies and the decline in university students’ well-being is currently an internationally shared concern. Among the most important factors influencing students’ well-being are time and effort management skills as well as psychological flexibility. The aim of this study was to compare two different study skills courses. One focused on time and effort management (TIMA) and the other on psychological flexibility (WELLS). The aim was to gain an understanding of what kinds of students apply for these two study skills courses and whether different student profiles gain different benefits from these courses.MethodsA pre- and post-test design was utilized to explore changes in time and effort management skills and psychological flexibility during the respective courses. Students’ final reports from the courses were additionally analysed qualitatively.ResultsThe results showed that students’ organised studying improved in both courses with no significant differences between TIMA and WELLS. Psychological flexibility increased only in the WELLS. A cluster analysis across all participants produced four different clusters of students based on their psychological flexibility and time and effort management scores at the beginning of the course. There were differences between the profiles in changes in psychological flexibility and organised studying in the two courses and during both courses students gained several benefits from these courses.DiscussionThis study showed that both time and effort management training and psychological flexibility training can produce multiple benefits for students. The results are further discussed, and practical implications are presented.